Preparation method and application of cross-basement membrane back-diffusion in-situ growth ZIF modified polyvinyl polyamide positively charged nanofiltration membrane
The preparation method of the ZIF-modified polyvinyl polyamide positively charged nanofiltration membrane grown in situ by reverse diffusion across the basement membrane has solved the problem of insufficient selectivity and permeability flux during magnesium-lithium separation, and achieved efficient magnesium-lithium separation and high water flux.
Patent Information
- Application Number
- CN202510626486.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-06-27
- Estimated Expiration
- 2045-05-15
AI Technical Summary
When the existing nanofiltration membrane is separated by magnesium lithium ions in salt lake brine, the separation selectivity is low and the permeability flux is insufficient, making it difficult to ensure efficient separation of magnesium lithium and high water flux at the same time.
The preparation method of the polyvinyl polyamide positively charged nanofiltration membrane modified by reverse diffusion in situ growth of ZIF across the basement membrane is adopted. Through the technology of reverse phase interface polymerization and reverse diffusion in situ growth of ZIF, uniformly distributed ZIF particles are formed, which improves the permeability flux of the membrane and the retention rate of magnesium ions.
On the basis of ensuring the separation performance of magnesium lithium, the permeability flux of water is significantly improved, non-selective defects caused by nanoparticle agglomeration are avoided, and the separation performance of the membrane is improved.
Smart Images

Figure CN120204962A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nanofiltration membranes, and particularly to a preparation method and application of a positively charged nanofiltration membrane of polyvinyl polyamide modified by in-situ growth of ZIF by cross-matrix membrane reverse diffusion. Background Art
[0002] In the field of extracting lithium from salt lake brine, the nanofiltration membrane technology is regarded as the core solution for realizing efficient separation of magnesium and lithium due to its advantages of low energy consumption and ion selectivity. Based on the synergistic mechanism of Donnan effect and size sieving effect, traditional nanofiltration membranes can preferentially retain high-valence ions (such as Mg2+) while allowing monovalent ions (such as Li+) to permeate. However, in the actual salt lake brine system, the difference in the hydrated radii of magnesium and lithium ions is small, resulting in a sharp decline in the separation selectivity of conventional polyamide nanofiltration membranes for magnesium and lithium.
[0003] Currently, commercial nanofiltration membranes enhance the retention of magnesium ions by reducing the pore size. However, due to the mutually restrictive problem of permeability-selectivity, the permeation flux of the membrane will decrease sharply. In addition, most commercial nanofiltration membranes have a negative charge on the surface, which is more unfavorable for the retention of magnesium ions. In addition, the traditional polysulfone substrate membrane has a high cost and a complex preparation process. Therefore, using a low-cost and mechanically good polyethylene ion battery separator (PE) to replace the polysulfone membrane has become a research hotspot.
[0004] However, the inertness of the PE surface results in a loose and porous polyamide layer formed by conventional interfacial polymerization, with a low retention rate of magnesium ions. Some researchers have tried to construct a dense positive charge layer on polyethylene (PE) by reverse interfacial polymerization using traditional diamine monomers such as piperazine (PIP) and trimesoyl chloride (TMC). The obtained multilayer composite polyamide (TFC-PE / PA) nanofiltration membrane still has a negative charge and poor permeation flux, only 4.8L·m -2 ·h -1 ·bar -1 , and researchers have tried to improve the water flux by directly doping nanoparticles. However, when traditional nanomaterials are mixed into the aqueous phase or oil phase for interfacial polymerization, the agglomeration of nanoparticles will inevitably occur, forming non-selective defects, thereby reducing the separation performance of the membrane. Therefore, how to improve the water permeation flux while ensuring the magnesium-lithium separation performance is one of the difficulties in the current magnesium-lithium separation technology. Summary of the Invention
[0005] In view of the above deficiencies, the present invention provides a preparation method and application of a positively charged nanofiltration membrane of polyvinyl polyamide modified by in-situ growth of ZIF by cross-matrix membrane reverse diffusion, which greatly improves the water permeation flux on the premise of ensuring the magnesium-lithium separation performance.
[0006] A preparation method of a positively charged nanofiltration membrane of polyvinyl polyamide modified by in-situ growth of ZIF by cross-matrix membrane reverse diffusion, the preparation process of which includes the following steps:
[0007] First, an organic phase solution containing trimesoyl chloride monomer is cast on one surface of a support bottom membrane, and then a mixed aqueous phase solution containing polyethyleneimine monomer and zinc nitrate hexahydrate is cast. Reverse interfacial polymerization is carried out. After the reaction is completed, reverse diffusion of an imidazole solution is carried out on the surface of the support bottom membrane on the side where interfacial polymerization has not been carried out, and a composite nanofiltration membrane with uniformly grown ZIF is in-situ grown, that is, a positively charged nanofiltration membrane of polyvinyl polyamide modified by in-situ growth of ZIF through reverse diffusion across the base membrane.
[0008] The specific steps are as follows:
[0009] Step 1: Prepare a mixed aqueous solution of polyethyleneimine and zinc ions as the aqueous phase solution, prepare an alkane solution of aromatic acyl chloride as the organic phase solution, and prepare a water or alcohol solution containing imidazole monomer as the ligand solution for reverse diffusion;
[0010] Step 2: Cast the organic phase solution prepared in Step 1 on either surface of a porous polyolefin support bottom membrane, soak for a period of time, and remove the excess solution;
[0011] Step 3: Use the aqueous phase solution prepared in Step 1 to cast on the support bottom membrane infiltrated with the organic phase monomer obtained in Step 2. After reverse interfacial polymerization for a period of time, remove the excess solution;
[0012] Step 4: Cast the imidazole solution prepared in Step 1 on the surface of the porous polyolefin support bottom membrane obtained in Step 3 on the side where interfacial polymerization has not been carried out. After reverse diffusion in-situ growth for a period of time, remove the excess solution;
[0013] Step 5: Heat-treat and alcohol-activate the nanofiltration membrane obtained in Step 4 to obtain a positively charged nanofiltration membrane of polyvinyl polyamide modified by in-situ growth of ZIF through reverse diffusion across the base membrane;
[0014] The molecular weight of the polyethyleneimine monomer is from 700 to 70,000 daltons, the acyl chloride monomer is trimesoyl chloride, the alkane solution is one or more of n-hexane, cyclohexane, ethyl acetate, and dodecane, the imidazole monomer is one or more of dimethylimidazole and benzimidazole, and the ligand solution for dissolving the imidazole monomer is one or more of deionized water, methanol, and ethanol;
[0015] In Step 1: In the configured organic phase solution, the concentration of trimesoyl chloride is 0.01 - 0.1 w / v% (i.e., the dosage ratio of aromatic acyl chloride to alkane in the organic phase solution is 0.01 - 0.1 g: 100 mL), the concentration of the configured aqueous phase polyethyleneimine solution is 0.1 - 2.0 w / v% (i.e., the dosage ratio of polyethyleneimine to water in the aqueous phase solution is 0.1 - 2.0 g: 100 mL), the concentration of zinc ions in the configured aqueous phase is 0.0002 - 0.002 mol / L, and the concentration of the configured imidazole ligand is 0.003 - 0.03 mol / L;
[0016] In Step 2: The coating time of the organic phase solution is 1 - 10 minutes;
[0017] In Step 3: The coating time of the aqueous phase solution is 1 - 10 minutes;
[0018] In Step 4: The coating time of the imidazole solution is 1 - 60 minutes;
[0019] In Step 5: The drying temperature is 50 - 80 °C, the drying time is 10 - 20 minutes, the type of alcohol used for alcohol activation is isopropyl alcohol, and the alcohol activation time is 1 - 3 minutes;
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] (1) Using a polyolefin bottom film, it saves costs, has relatively mild operating conditions, a simple preparation process, and is suitable for industrial production.
[0022] (2) Due to the trade - off effect, the rejection of magnesium ions will significantly decrease during the process of increasing the permeation flux. We adopted the method of inverse interfacial polymerization combined with in - situ growth of ZIF by cross - substrate membrane counter - diffusion to break this balance. It not only ensures the rejection rate of magnesium ions but also greatly improves the permeation flux. Moreover, the ZIF particles grown by this method are more evenly distributed, effectively avoiding the interfacial gaps caused by agglomeration phenomena.
[0023] (3) The positively charged nanofiltration membrane of polyvinyl polyamide modified by in - situ growth of ZIF by cross - substrate membrane counter - diffusion is beneficial to maintaining a high water flux, magnesium ion rejection, and low lithium ion rejection.
[0024] The present invention discloses a preparation method of a positively charged nanofiltration membrane of polyvinyl polyamide modified by in - situ growth of ZIF by cross - substrate membrane counter - diffusion. An aqueous phase solution containing polyethyleneimine monomers rich in amino groups is used to improve the rejection of magnesium ions by the composite membrane through the method of inverse interfacial polymerization. In - situ growth of ZIF by counter - diffusion is used to improve the interfacial compatibility between the MOF material and the polyamide layer, and an additional water channel is provided to enhance the hydrophilicity of the membrane, thereby greatly improving the permeation flux of the membrane. Description of the Drawings
[0025] Figure 1 This is a schematic flow chart for preparing the nanofiltration membrane of the present invention.
[0026] Figure 2 These are SEM images of the membrane surfaces of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3.
[0027] Figure 3 These are comparative diagrams of the water contact angles of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3.
[0028] Figure 4 These are comparative diagrams of the roughness of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3.
[0029] Figure 5 These are infrared spectra of Example 1 and Comparative Example 1.
[0030] Figure 6 These are comparative diagrams of the water flux and salt rejection performance of Examples 1-4 and Comparative Examples 1-4.
[0031] Figure 7 These are the Mg 2+ / Li + separation performance diagrams of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3.
[0032] Figure 8 These are the pressure resistance performance and operation stability performance of Example 1. Detailed implementation manners
[0033] In order to describe the present invention in more detail, the following will be described in detail, but not limited thereto. For those not elaborated in detail in the present invention, they shall follow the conventional techniques in the art.
[0034] As Figure 1 shown, the method of the present invention includes the following steps:
[0035] Step 1: Prepare an aqueous solution of polyethyleneimine and zinc ions as the aqueous phase solution, prepare an alkane solution of aromatic acyl chloride as the organic phase solution, and prepare a water or alcohol solution containing imidazole monomer as the imidazole solution for counter-diffusion;
[0036] Step 2: Cast the organic phase solution prepared in Step 1 on one surface of the porous polyolefin support substrate membrane, remove the excess solution after infiltration;
[0037] Step 3: Use the aqueous phase solution prepared in Step 1 to cast the support substrate membrane infiltrated with the organic phase monomer obtained in Step 2. After inverse interfacial polymerization, remove the excess solution to obtain a porous polyolefin support material;
[0038] Step 4: Coat the surface of the porous polyolefin support material obtained in Step 3 on the side where interfacial polymerization has not been carried out with the prepared reverse-diffusion imidazole solution. After in-situ growth by reverse diffusion, remove the excess solution to obtain a nanofiltration membrane;
[0039] Step 5: Heat-treat and alcohol-activate the nanofiltration membrane obtained in Step 4 to obtain a positively charged nanofiltration membrane of polyvinyl polyamide modified by in-situ growth of ZIF by reverse diffusion across the substrate membrane.
[0040] Materials used in the present invention: There are no special restrictions on the sources of all raw materials in the present invention and the following examples, and they can be commercially available.
[0041] Method for detecting the membrane flux of the highly selective lithium-magnesium separation membrane: Use a membrane permeation selectivity test system to test the water permeation flux and salt rejection rate of the membrane. The test system includes a pump, a membrane cell, pipelines, a regulating valve, a pressure and flow detector. Among them, the effective membrane area for testing is 19.64 cm 2 , the test pressure is 6 bar, and the test temperature is 25 ± 0.5 °C. The salt concentrations for testing the single-salt rejection rate: the concentrations of MgCl2 and LiC1 are both 1000 ppm.
[0042] Example 1:
[0043] Prepare 50 mL of a n-hexane solution containing 0.05% trimesoyl chloride (i.e., the dosage ratio of trimesoyl chloride to n-hexane is 0.05 g: 100 mL) as the organic phase solution, prepare 50 mL of an aqueous solution containing 1.0% polyethyleneimine (molecular weight 70000) and 0.0006 mol / L zinc nitrate hexahydrate as the aqueous phase solution (i.e., the dosage ratio of polyethyleneimine to water is 1.0 g: 100 mL), and prepare 50 ml of an aqueous solution of 2-methylimidazole containing 0.009 mol / L as the reverse-diffusion ligand solution.
[0044] First, coat the organic phase solution on the surface of the polyolefin support membrane. After 4 minutes, remove the excess solution. Then coat the aqueous phase solution on the membrane surface wetted by the organic phase and carry out an interfacial polymerization reaction for 4 minutes. After removing the excess solution, dry the liquid on the membrane surface. Then turn the membrane to the side where interfacial polymerization has not been carried out and coat it with the 2-methylimidazole ligand aqueous solution and react for 30 minutes. After removing the excess solution, place the membrane in an oven at 60 °C and dry it for 15 minutes. After drying, soak it in isopropanol for 1 minute and wash the membrane surface with water for testing.
[0045] The test results are as follows: the water flux is 15.11 L·m -2 ·h -1 ·bar -1 , the rejection of magnesium chloride is 96.6%, and the rejection of lithium chloride is 40.1%.
[0046] AsFigure 2 As shown, the membrane surface of Example 1 exhibits significant wrinkled morphological features. This unique surface microstructure effectively increases the surface roughness of the membrane material, which is further verified by Figure 4 the atomic force microscope roughness analysis results. The improvement of surface roughness is beneficial to enhancing the surface wettability of the material, which is consistent with Figure 3 the contact angle test results in
[0047] Example 2: Referring to Example 1, the difference is that the back-diffusion time of the 2-methylimidazole ligand aqueous solution is 45 minutes.
[0048] The test results are: water flux 14.77 L·m -2 ·h -1 ·bar -1 , the rejection of magnesium chloride is 95.7%, and the rejection of lithium chloride is 42.2%.
[0049] Example 3: Referring to Example 1, the difference is that the back-diffusion time of the 2-methylimidazole ligand aqueous solution is 60 minutes.
[0050] The test results are: water flux 13.8 L·m -2 ·h -1 ·bar -1 , the rejection of magnesium chloride is 95.85%, and the rejection of lithium chloride is 40%.
[0051] Example 4: Referring to Example 1, the difference is that the 2-methylimidazole ligand solution is a 50% methanol and water mixed solution.
[0052] The test results are: water flux 14.78 L·m -2 ·h -1 ·bar -1 , the rejection of magnesium chloride is 95.65%, and the rejection of lithium chloride is 41%.
[0053] Comparative Example 1:
[0054] Place 50 mL of a n-hexane solution containing 0.05% trimesoyl chloride as the organic phase solution, and prepare 50 mL of an aqueous solution containing 1.0% polyethyleneimine (molecular weight 70000) as the aqueous phase solution.
[0055] First, the organic phase solution is cast on the surface of the polyolefin support membrane. After maintaining for 4 minutes, the excess solution is removed. Then, the aqueous phase solution is cast on the surface of the membrane infiltrated by the organic phase, and after the interfacial polymerization reaction for 4 minutes, the excess solution is removed. The liquid on the membrane surface is dried, and the membrane is placed in an oven at 60 °C and dried for 15 minutes. After drying, it is soaked in isopropanol for 1 minute, and the membrane surface is washed with water for testing.
[0056] The test results are as follows: the water flux is 5.8 L·m -2 ·h -1 ·bar -1 , the rejection rate for magnesium chloride is 97.9%, and the rejection rate for lithium chloride is 50.2%.
[0057] Comparative Example 2: Referring to Comparative Example 1, the difference is that the prepared aqueous phase solution is a mixed aqueous solution of 1.0% polyethyleneimine (molecular weight 70,000) and 0.0006 mol / L zinc nitrate hexahydrate.
[0058] The test results are as follows: the water flux is 7.65 L·m -2 ·h -1 ·bar -1 , the rejection rate for magnesium chloride is 96.1%, and the rejection rate for lithium chloride is 38.5%.
[0059] Comparative Example 3:
[0060] Prepare 50 mL of a n-hexane solution containing 0.05% trimesoyl chloride as the organic phase solution, prepare 50 mL of a mixed aqueous solution of 1.0% polyethyleneimine (molecular weight 70,000) and 0.0006 mol / L zinc nitrate hexahydrate as the aqueous phase solution, and prepare 50 mL of an aqueous solution of 2-methylimidazole containing 0.009 mol / L as the anti-diffusion ligand solution.
[0061] First, the organic phase solution is cast on the surface of the polyolefin support membrane. After maintaining for 4 minutes, the excess solution is removed. Then, the aqueous phase solution is cast on the surface of the polyolefin support membrane infiltrated by the organic phase, and after the interfacial polymerization reaction for 4 minutes, the excess solution is removed. The liquid on the membrane surface is dried, and the 2-methylimidazole ligand aqueous solution is cast on the side where the interfacial polymerization has been carried out and reacted for 30 minutes, and then the excess solution is removed. The membrane is placed in an oven at 60 °C and dried for 15 minutes. After drying, it is soaked in isopropanol for 1 minute, and the membrane surface is washed with water for testing.
[0062] The test results are as follows: the water flux is 11.2 L·m -2 ·h -1 ·bar -1 , the rejection rate for magnesium chloride is 96.05%, and the rejection rate for lithium chloride is 37.65%.
[0063] Comparative Example 4: Prepare 50 mL of a n-hexane solution containing 0.05% trimesoyl chloride as the organic phase solution, and prepare 50 mL of a mixed solution containing 1.0% polyethyleneimine (molecular weight 70,000) and 0.02% ZIF-8 nanoparticles as the aqueous phase solution. First, pour the organic phase solution onto the surface of the polyolefin support membrane, remove the excess solution after 4 minutes, pour the aqueous phase solution onto the surface of the membrane infiltrated with the organic phase, remove the excess solution after reacting for 4 minutes, blow dry the liquid on the membrane surface, place the membrane in an oven at 60 °C and dry for 15 minutes. After drying, soak it in isopropanol for 1 minute, and wash the membrane surface with water for testing.
[0064] The test results are as follows: the water flux is 11.2 L·m -2 ·h -1 ·bar -1 , the rejection of magnesium chloride is 96.5%, and the rejection of lithium chloride is 42.8%.
[0065] It can be seen from the following Figure 6 that Examples 1, 2, 3, and 4 have higher water fluxes compared to Comparative Examples 1, 2, 3, and 4, and maintain a relatively high magnesium ion rejection rate. It can also be seen from Figure 7 that Example 1 has a relatively high magnesium-lithium separation ratio of 17.65, slightly lower than 21 of Comparative Example 1, but its water permeation flux is 2-3 times higher than that of Comparative Example 1, showing a greater advantage. In the infrared characterization diagram, the Zn-N stretching vibration mode of Example 1 can be observed at 421 cm -1 , indicating the successful growth of ZIF-8 nanoparticles. It can be seen from the electron microscope images that the surface of Example 1 has more wrinkled structures, greatly increasing its roughness. The roughness values of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 are 95 nm, 12.3 nm, 19.7 nm, and 61.9 nm respectively, indicating that Example 1 has better hydrophilicity. This can also be demonstrated from the water contact angle diagram. The contact angles of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 are 69°, 94°, 84°, and 87° respectively. Example 1 has the smallest contact angle, the best hydrophilicity, and the best permeation performance. In addition, Example 1 also has good pressure resistance and operating stability.
Claims
1. A method for preparing a positively charged nanofiltration membrane of polyvinyl polyamide modified by in-situ growth of ZIF by reverse diffusion across a basement membrane, characterized in that: The following steps are involved: First, an organic phase solution containing trimesoyl chloride monomer is coated on one surface of a supporting base membrane, and then a mixed aqueous phase solution containing polyethyleneimine monomer and zinc nitrate hexahydrate is coated to perform reverse interfacial polymerization. After the reaction is completed, the imidazole solution is reversely diffused on the side of the supporting base membrane where no interfacial polymerization is performed, and a composite nanofiltration membrane with uniformly grown ZIF is formed in situ, that is, a polyethylene polyamide positively charged nanofiltration membrane modified by reverse diffusion and in situ growth of ZIF across the base membrane.
2. A method for preparing a positively charged nanofiltration membrane of polyethylene polyamide modified by in-situ growth of ZIF by reverse diffusion across a substrate membrane, characterized in that: The following steps are involved: Step 1: preparing a mixed aqueous solution of polyethyleneimine and zinc ions as an aqueous phase solution, preparing an alkane solution of aromatic acid chloride as an organic phase solution, and preparing a water or alcohol solution containing imidazole monomer as an imidazole solution for reverse diffusion; Step 2: coating the organic phase solution prepared in step 1 on one surface of the porous polyolefin support base film, and removing the excess solution after infiltration; Step 3: Use the aqueous solution prepared in step 1 to cast the support base film soaked with the organic phase monomer obtained in step 2, and after reverse phase interfacial polymerization, remove the excess solution to obtain a porous polyolefin support material; Step 4: coating the reverse diffusion imidazole solution prepared in step 1 on the surface of the porous polyolefin support material obtained in step 3 which has not been subjected to interfacial polymerization, and removing the excess solution after reverse diffusion in situ growth to obtain a nanofiltration membrane; Step 5: The nanofiltration membrane obtained in step 4 is subjected to heat treatment and alcohol activation to obtain a polyvinyl polyamide positively charged nanofiltration membrane modified by in-situ growth of ZIF through reverse diffusion across the base membrane.
3. The preparation method according to claim 2, characterized in that: In step 1, the molecular weight of the polyethyleneimine monomer is 700 to 70,000; The aromatic acid chloride is trimesoyl chloride, and the solvent in the alkane solution of the aromatic acid chloride is one or more of n-hexane, cyclohexane, ethyl acetate, and dodecane; The imidazole monomer is one or more of dimethylimidazole and benzimidazole, the water is deionized water, and the alcohol is one or more of methanol and ethanol.
4. The preparation method according to claim 2, characterized in that: In step 1, the dosage ratio of polyethyleneimine to water in the aqueous solution is 0.1-2.0 g:100 mL; the zinc ion concentration in the aqueous solution is 0.0002-0.002 mol / L; The ratio of aromatic acid chloride to alkane in the organic phase solution is 0.01-0.1 g:100 mL; The imidazole ligand concentration in the counter-diffusion imidazole solution is 0.003-0.03 mol / L.
5. The preparation method according to claim 2, characterized in that: In step 2: the pouring time of the organic phase solution is 1 to 10 minutes.
6. The preparation method according to claim 2, characterized in that: In step 3: the pouring time of the aqueous solution is 1 to 10 minutes.
7. The preparation method according to claim 2, characterized in that: In step 4: the pouring time of the reverse diffusion imidazole solution is 1 to 60 minutes.
8. The preparation method according to claim 2, characterized in that: In step 5: the conditions of heat treatment are: drying temperature is 50-80°C, and drying time is 10-20 minutes.
9. The preparation method according to claim 2, characterized in that: In step 5: the alcohol type used for alcohol activation is isopropanol, and the alcohol activation time is 1-3 minutes.
10. Use of a polyvinyl polyamide positively charged nanofiltration membrane modified by in-situ growth ZIF through reverse diffusion across a substrate membrane prepared by the preparation method according to any one of claims 1 to 9 in magnesium and lithium separation in water treatment.
Citation Information
Patent Citations
Preparation method for back-diffusion in-situ self-assembled MOFs nanofiltration membrane
CN105126638A
MOFs compound film, preparation method and application thereof
CN107441952A
ZIF-8 / PDMS mixed matrix pervaporation membrane as well as preparation method and application thereof
CN113351037A
Method for preparing nanofiltration membrane based on polyolefin composite polyamide membrane in-situ growth ZIF
CN114225699A
Polyamide / polyolefin mixed matrix nanofiltration membrane and preparation method thereof
CN115487693A
Cited By
C-PEI-ZIF-8 mixed matrix membrane based on reverse filling method as well as preparation method and application of c-PEI-ZIF-8 mixed matrix membrane
CN121490598A
MOF (Metal Organic Framework) composite nanofiltration membrane based on chemical bonding structure and lithium-magnesium separation application of MOF composite nanofiltration membrane
CN122424730A